2014
DOI: 10.1186/1478-4505-12-52
|View full text |Cite
|
Sign up to set email alerts
|

The making of nursing practice Law in Lebanon: a policy analysis case study

Abstract: BackgroundEvidence-informed decisions can strengthen health systems, improve health, and reduce health inequities. Despite the Beijing, Montreux, and Bamako calls for action, literature shows that research evidence is underemployed in policymaking, especially in the East Mediterranean region (EMR). Selecting the draft nursing practice law as a case study, this policy analysis exercise aims at generating in-depth insights on the public policymaking process, identifying the factors that influence policymaking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Lebanon welcomed more than 1.2 million Syrian refugees registered with UNHCR from 2012 till the end of 2015 ( Figure 1 ), 5 , 6 and many more are present but without registration. 7 As the Lebanese Government has not permitted the establishment of formal camps, displaced Syrians remain dispersed all over the country in over 1,700 localities 8 all over the six districts, where Bekaa (Arsal) and North (Akkar), which include the most vulnerable, poor, and undeserved communities, 9 host the largest numbers (373,124) followed by Beirut (314,731). 10 In spite of its contemporary history of military and political conflicts as well as pressures on its infrastructure, Lebanon kept its borders open till October 2014, 7 , 11 , 12 after which it adopted a policy paper to limit and decrease the Syrian refugee population on the Lebanese land, secure Lebanese and Syrian people’s safety, and ease the burden placed on Lebanese people and economy.…”
Section: Resultsmentioning
confidence: 99%
“…Lebanon welcomed more than 1.2 million Syrian refugees registered with UNHCR from 2012 till the end of 2015 ( Figure 1 ), 5 , 6 and many more are present but without registration. 7 As the Lebanese Government has not permitted the establishment of formal camps, displaced Syrians remain dispersed all over the country in over 1,700 localities 8 all over the six districts, where Bekaa (Arsal) and North (Akkar), which include the most vulnerable, poor, and undeserved communities, 9 host the largest numbers (373,124) followed by Beirut (314,731). 10 In spite of its contemporary history of military and political conflicts as well as pressures on its infrastructure, Lebanon kept its borders open till October 2014, 7 , 11 , 12 after which it adopted a policy paper to limit and decrease the Syrian refugee population on the Lebanese land, secure Lebanese and Syrian people’s safety, and ease the burden placed on Lebanese people and economy.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Phase I of the study clearly indicated that the A-ASCOP was not suitable for use following the initial translation. Of the 26 items, seven items [3,5,6,7,8,13,17] confused the participants and did not preserve the meaning of the original ASCOP questionnaire. Although properly translated, five of the remaining items [2,4,9,10,15] needed to be rephrased ( Figure 1).…”
Section: Phase I Translation Expert Panel Endorsement and Back Tranmentioning
confidence: 99%
“…Lebanese nurse leaders have responded to the omissions and ambiguities in Decree 1655 by drafting an updated practice act with three categories of nurse delineated by level of preparation: nurse specialist (Master of Science in Nursing), nurse (Bachelor of Science in Nursing), and nurse assistant (Baccalaureate Technique Certificate). The draft updated decree lists nursing activities corresponding with the three levels of preparation (6). Neither the updated practice act, nor the draft qualification and specific scopes of nursing practice have been approved due to the political situation in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the Syrian crisis, there was a remarkable shortage in nursing, especially in the underserved areas of Lebanon. Pre‐crisis, the ratio of nurses (including midwives) was 1.8 per 1,000 population, the eighth lowest nursing density in the eastern Mediterranean region (El‐Jardali et al., ). In response, the Lebanese MoPH in coordination with the Order of Nurses in Lebanon (ONL) made concerted efforts to increase the number of nurses working in health organizations across Lebanon (Ammar et al., ).…”
mentioning
confidence: 99%